(untitled) (REMUNOM, 2025)
Family farming in the Amazon does not appear to have evolved over the centuries, as studies by past explorers and anthropologists have shown by past explorers. It is likely that the absence of financial management instruments and procedures, such as control, largely explains the low quality of life, well-being, and comfort, such as those of the distant past. This study aimed to analyze the financial control practiced by family farmers who participated in a family farming fair in Manaus. The survey method was used, with data collected through a questionnaire with close questions (about the demographic aspects of the production units, the revenue of these units, the challenges of the production units, their management and accounting aspects), analyzed with descriptive statistics and the results presented in frequency tables. The results showed that a) the workforce is composed of up to five people, b) it must have a maximum average monthly turnover of up to four minimum wages, c) the main challenges of the production units are logistical, and the division of labor, d) financial management is rudimentary or non-existent, e) without the assistance of accounting professionals. The conclusion shows that a few family farmers practiced financial control and some types of formal production planning.